2016
DOI: 10.1161/circimaging.116.005115
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Dysfunction Impairs Effort Tolerance Independent of Left Ventricular Function Among Patients Undergoing Exercise Stress Myocardial Perfusion Imaging

Abstract: Background RV and LV function are closely linked due to a variety of factors, including common coronary blood supply. Altered LV perfusion holds the potential to affect the RV, but links between LV ischemia and RV performance, as well as independent impact of RV dysfunction on effort tolerance are unknown. Methods and Results The population comprised 2051 patients who underwent exercise stress MPI and echo (5.5 ± 7.9 days), among whom 6% had echo-evidenced RV dysfunction. Global summed stress scores were nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 41 publications
(53 reference statements)
3
22
1
1
Order By: Relevance
“…In our study, the rate of hospitalization due to cardiac failure was higher in patients living at a high altitude than those at sea level. It is known that disruption in right ventricular functions impairs effort capacity (12). In our study, we observed that right cardiac dimensions were wider, and that PASP was higher in patients with cardiac failure who lived at intermediate high altitudes.…”
Section: Discussionsupporting
confidence: 50%
“…In our study, the rate of hospitalization due to cardiac failure was higher in patients living at a high altitude than those at sea level. It is known that disruption in right ventricular functions impairs effort capacity (12). In our study, we observed that right cardiac dimensions were wider, and that PASP was higher in patients with cardiac failure who lived at intermediate high altitudes.…”
Section: Discussionsupporting
confidence: 50%
“…Transthoracic echo was performed using commercial equipment (Philips ie33 [Andover, MA]). Echoes were interpreted by experienced investigators within a high-volume laboratory, for which expertise and reproducibility for quantitative LV and RV indices have been validated and applied in population-based research [ 12 , 14 , 15 ]. RV systolic function was quantified via TAPSE, RV-S’ and fractional area change (FAC), which were acquired in accordance with consensus guidelines [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…LV chamber size and function were quantified on echo based on standardized linear dimensions measured in parasternal long axis orientation, concordant with established methods validated in prior research [21,22]. LV mass was quantified using anteroseptal and posterior wall thickness and LV diastolic dimension, in accordance with necropsy validated methods [23].…”
Section: Plos Onementioning
confidence: 98%